The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fimmu.2018.01427
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Cathepsin Release Is Required for NLRP3-Inflammasome Activation by Mycobacterium tuberculosis in Infected Macrophages

Abstract: Lysosomal cathepsin B (CTSB) has been proposed to play a role in the induction of acute inflammation. We hypothesised that the presence of active CTSB in the cytosol is crucial for NLRP3-inflammasome assembly and, consequently, for mature IL-1β generation after mycobacterial infection in vitro. Elevated levels of CTSB was observed in the lungs of mice and rabbits following infection with Mycobacterium tuberculosis (Mtb) H37Rv as well as in plasma from acute tuberculosis patients. H37Rv-infected murine bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 84 publications
(120 reference statements)
2
86
0
1
Order By: Relevance
“…The ability to disrupt phagosomes seems important for inflammasome activation by Mtb, and it has been reported that phagosomal acidification is a prerequisite for the membrane damaging activity of ESX-1 6365 . Additionally, active cathepsin release from ruptured phagolysosomes is a suggested trigger for the NLRP3 inflammasome 24, 39, 40 . We therefore went on to investigate the possible involvement of phagosomal acidification and release of active cathepsins in inflammasome activation and pyroptosis by Mtb.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to disrupt phagosomes seems important for inflammasome activation by Mtb, and it has been reported that phagosomal acidification is a prerequisite for the membrane damaging activity of ESX-1 6365 . Additionally, active cathepsin release from ruptured phagolysosomes is a suggested trigger for the NLRP3 inflammasome 24, 39, 40 . We therefore went on to investigate the possible involvement of phagosomal acidification and release of active cathepsins in inflammasome activation and pyroptosis by Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal damaging agents are one of the most clinically relevant classes of NLRP3 triggers 83 . Cathepsin release from damaged lysosomes, especially of Cathepsin B, is one commonly proposed connection, although how this further causes K+ efflux has been unclear 24, 39, 40 . One main source of this confusion is the widespread use of the Cathepsin B inhibitor Ca-074-Me, which appears to inhibit NLRP3 activation independent of Cathepsin B inhibition (our results and 28, 4143) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of human pathogens, including Mtb (36) stimulate the production of IL-1β by macrophages and other immune cells, such as dendritic cells and neutrophils. Previous studies have shown that Mtb stimulates IL-1β production by macrophages with the involvement of activated NLRP3, caspase 1 and cathepsin B in an ESAT-6 secretion system (ESX)-1 dependent manner (17, 18). In this study, we have demonstrated with data from both in vitro macrophage infection with Mtb and in vivo mouse intranasal treatment with ESAT-6 or infection with Mtb that ESAT-6 is required for Mtb- induced mature IL-1β production by macrophages with the involvement of K+ efflux and activated NLRP3 (17, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Levando em conta que (AMARAL, E. P. et al, 2018) demonstraram, em modelo murino de TB que a liberação de catepsinas lisossomais é um evento chave na ativação de NLRP3 por Mtb, testamos essa via no nosso modelo de MDM humanos e confirmamos que a liberação de catepsina B é um evento chave na ativação do inflamassoma frente a Mtb, e que esse mecanismo possivelmente não afeta apenas a ativação do NLRP3 mas também de outros receptores, sendo que o efeito inibitório é maior quando comparado a inibição especifica do NLRP3. É interessante destacar que foi reportado recentemente que a liberação de catepsinas ativa o NLRC4 em um modelo murino de infecção por Salmonella (LAGE et al, 2013), sugerindo que, como ja observado por (MASTER et al, 2008) do epitélio e na polarização dos linfócitos T CD4 + em células efetoras Th1 produtoras de IFN-γ.…”
Section: O Receptor Nlrc4 Está Presente Nos Agregados De Asc Induzidounclassified